Vaccination for hepatitis C virus: closing in on an evasive target - Halliday, John (2011)
Hepatitis C virus (HCV) infects more than 170 million people globally and is a leading cause of liver cirrhosis, transplantation and hepatocellular carcinoma. Current gold-standard therapy often fails, has significant side effects in many cases and is expensive. No vaccine is currently available. The fact that a significant proportion of infected people spontaneously control HCV infection in the setting of an appropriate immune response suggests that a vaccine for HCV is a realistic goal. A comparative analysis of infected people with distinct clinical outcomes has enabled the characterization of many important innate and adaptive immune processes associated with viral control. It is clear that a successful HCV vaccine will need to exploit and enhance these natural immune defense mechanisms. New HCV vaccine approaches, including peptide, recombinant protein, DNA and vector-based vaccines, have recently reached Phase I/II human clinical trials. Some of these technologies have generated robust antiviral immunity in healthy volunteers and infected patients. The challenge now is to move forward into larger at-risk or infected populations to truly test efficacy.